Role of Artificial Intelligence in Livestock and Poultry Farming - Patel , Hrishitva; Samad, Abdul; Muhammad Hamza; Ayesha Muazzam; Harahap, Muhammad Khoiruddin (Sinkron : jurnal dan penelitian teknik informatika, 2022)
One of the technologies, artificial intelligence (AI), requires quick adoption in the livestock sector. The use of AI technology can be highly beneficial in a number of key areas in the livestock business, including monitoring, forecasting, optimizing the growth of farm animals, contend with pests, diseases, threats of biosecurity, and monitoring farm animals and farm management. Livestock farms will be helped by artificial intelligence to gather and analyses of data in order to precisely forecast consumer behavior, including purchasing patterns, top trends, etc. Operation of farm will be done by using automatic means which directly minimize the expense and increase the quality of egg, milk and meat products but this system needs some extra investment to start.